Predictive Examination of Phonological Awareness Among Hebrew-Speaking Kindergarten Children - Wasserstein, Dorin; Lipka, Orly (Frontiers in Psychology, 2019)
This short longitudinal study aimed to examine the role of cognitive, early literacy and language skills to phonological awareness (PA) among Hebrew speaking children at the Early (Early K) and end (End K) of kindergarten. The study also examined predictive relationships between cognitive, early literacy and language skills to PA at these two time points. Forty-one native Hebrew-speaking children (twenty-eight boys) between the ages of five and six were recruited from two kindergarten classes and were followed longitudinally from early to late kindergarten. They were administered measure of language (vocabulary), literacy (letter naming, phonological awareness), and cognition (object naming and, working memory and executive functioning). The results demonstrated the rapid growth of PA skills among children who speak Hebrew during the kindergarten year (Early K- End of K). Strong-moderate positive correlations were found between PA and both letter naming and EF at Early K. Strong correlation between letter naming and PA was found at End K. Regression analyses demonstrated that letter naming and executive functioning at Early K were the most significant predictor of PA at Early K, and that letter naming was the most significant predictor at End K. Theoretical and practical implications of these findings are discussed with relation in general and to the Hebrew language specifically.